2018
DOI: 10.1016/j.jaci.2017.12.972
|View full text |Cite|
|
Sign up to set email alerts
|

The activation and function of IL-36γ in neutrophilic inflammation in chronic rhinosinusitis

Abstract: Increased production and activation of IL-36γ may act on neutrophils and further exaggerate neutrophilic inflammation in CRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
159
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(176 citation statements)
references
References 67 publications
(139 reference statements)
15
159
2
Order By: Relevance
“…27 Wang et al confirmed that both eosinophilic and noneosinophilic CRSwNP in Wuhan, China had elevated expression of IFN-γ and IL-17A compared with control, and noneosinophilic CRSwNP had even higher IFN-γ and IL-17A expression compared to eosinophilic CRSwNP. 34 Consistently, Shi et al and Ma et al found that Th1 and Th17 cell counts, as well as Tc1 and Tc17 cell counts, were increased in noneosinophilic CRSwNP versus eosinophilic CRSwNP and control in Chinese. 37,57 The number of ILC2s in noneosinophilic CRSwNP was comparable to that in healthy controls, but decreased as compared with that in eosinophilic CRSwNP.…”
Section: Immune Polarization In Crsmentioning
confidence: 73%
See 4 more Smart Citations
“…27 Wang et al confirmed that both eosinophilic and noneosinophilic CRSwNP in Wuhan, China had elevated expression of IFN-γ and IL-17A compared with control, and noneosinophilic CRSwNP had even higher IFN-γ and IL-17A expression compared to eosinophilic CRSwNP. 34 Consistently, Shi et al and Ma et al found that Th1 and Th17 cell counts, as well as Tc1 and Tc17 cell counts, were increased in noneosinophilic CRSwNP versus eosinophilic CRSwNP and control in Chinese. 37,57 The number of ILC2s in noneosinophilic CRSwNP was comparable to that in healthy controls, but decreased as compared with that in eosinophilic CRSwNP.…”
Section: Immune Polarization In Crsmentioning
confidence: 73%
“…26 The recently published study by Wang et al demonstrated that increased production and activation of epithelial cell-derived IL-36γ may act on neutrophils and further amplify neutrophilic inflammation in CRS (Fig 2). 34 IL-17A was able to upregulate the expression of IL-36γ in nasal epithelial cells in vitro , which may further promote neutrophilic inflammation in CRS. 34 Neutrophils were found to produce TGF-β2 in sinonasal mucosa, which may be involved in fibrosis in CRSsNP and noneosinophilic CRSwNP.…”
Section: Immune Polarization In Crsmentioning
confidence: 91%
See 3 more Smart Citations